1969
DOI: 10.1002/bit.260110410
|View full text |Cite
|
Sign up to set email alerts
|

Fluid dynamics of anaerobic fermentation

Abstract: SummaryIn beer fermentation, yeast cells are kept in suspension, despite their higher density, by natural agitation created by ascending CO, bubbles. Yeast cells are unable to nucleate bubbles but instead release Cot in a soluble form in such a way that the medium tends to become supersaturated.A higher concentration of yeast cells and the presence of solid particles cause the formation of bubbles at the bottom of the fermenter and practically only there. The rising bubbles grow and accelerate by sweeping the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…This was supported by the observed flow pattern. Variations in the geometry led to different flow fields, as the lees kept settling at the deepest point and with that the bubble nucleation sites moved as well [1]. This is in accordance with the general bubble nucleation theory.…”
Section: Driving Forces For the Flowsupporting
confidence: 85%
See 2 more Smart Citations
“…This was supported by the observed flow pattern. Variations in the geometry led to different flow fields, as the lees kept settling at the deepest point and with that the bubble nucleation sites moved as well [1]. This is in accordance with the general bubble nucleation theory.…”
Section: Driving Forces For the Flowsupporting
confidence: 85%
“…In-situ flow investigation of bubble-driven liquid flow processes in large scale is a challenging and expensive task. Therefore only lab-scale flow pattern analyses were performed on fermenting media in earlier studies [1,2]. Their findings indicated that bubble formation is primarily visible from settled lees.…”
Section: Driving Forces For the Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships expressed in eqs. (7) and (8) can be used to estimate a fermentor's efficiency as a settling device. At the maximum flow velocity permissible to maintain maximum suspended cell density (F/V),,,ax ( d ) gives a measurement of the settling velocity which cell particles must have to avoid washout.…”
Section: Settling Eficiency and Settling Ratesmentioning
confidence: 99%
“…The process is characterizes by different temperature levels and local temperature, velocity and concentration differences. The resulting flow in fermenters strongly influences the heat transfer and the transport of yeast cells [1].…”
Section: Introductionmentioning
confidence: 99%